Influence of Annealing Speed on Magnetic Properties in Submicron Sized Fe-B Particles - Miyazaki, T.; Ajia, S.; Masumoto, C.; Endo, Y.; Muroga, S. (Transaction of the Magnetics Society of Japan Special Issues, 2025)
This paper reports the effect of annealing speed on the structure, and magnetic properties of submicron sized amorphous Fe-B particles synthesized by a chemical reduction method. The shape of the synthesized particles was spherical, and their median size became approximately 708 nm. The DSC curve of the particles showed a crystallization temperature of 463 °C. The structure of the particles maintained an amorphous state at an annealing speed of less than 100 °C /min, while α-Fe and Fe3B coexisted at an annealing speed of 200–400°C/min. As the speed increased up to 100°C/min, the saturation magnetization and the intrinsic permeability of the particles increased to 153 emu/g and 17, respectively, and their coercivity decreased to 23 Oe. These results demonstrate that the magnetic properties of Fe-B particles can be improved markedly by the relaxation of internal stress in the particles as the range of annealing speed between 50-100 °C /min below crystallization temperature.